The process of theorizing, reflections and conclusions in the degree projects - César Valdés, Julio Cesar; Burgos Zambrano, Débora Judith (Conexiones UG, 2024)
The process of theorizing, reflections and conclusions in a degree project involves the construction of a solid theoretical base, critical reflection on the methodology and results, and the presentation of conclusions that contribute to existing knowledge and guide future research. The objective of this article is to analyze the importance and significance of the process of theorizing, reflections and conclusions in degree projects. Both the stated objective and the methodology used allow us to state as results that theories are a set of manifestations and formulations related to each other that delimit, detail, relate and manifest different phenomena of interest to study, which are developed and expanded from customs, personal habits, perception and preexisting knowledge. Reflections, for their part, play a crucial role in degree projects, allowing students to analyze, interpret and discuss the findings obtained throughout the research. The conclusions are where the results obtained are consolidated and final reflections on the research carried out are offered. Finally, it is concluded that the process of theorization, reflection and conclusions provide the opportunity to highlight the significant contribution of research to the field of study and propose recommendations for future research.